Impact of Income Growth and Economic Reform on Nutrition Intake in Urban China : 1986-2000 - Xin Meng; Xiaodong Gong; Youjuan Wang (Institute for the Study of Labor (IZA), 2004)
Although urban China has experienced a rapid income growth over the last twenty years, nutrition intake for the low income group declined in the 1990s. Does this imply a zero or negative income elasticity for the low income group? This paper examines this issue using large representative sample of repeated cross-sectional data for the period 1986-2000. It is found that income elasticities of calorie consumption for urban households are far from zero, and the lower the income level the higher the income elasticity. The main reason for the reduction in calorie consumption for the low income group in the early 1990s was a sharp increase in food price. In addition, in the mid to late 1990s large scale social welfare reform increased households? need to pay for education, medical, housing expenses and the need to save for future consumption and income uncertainty. These factors seem to have played an important role in suppressing nutrition consumption of the low income group during this period.
Keywords: I31; O15; O40; D31; 330; poverty; income growth; inequality; China; Städtische Armut; Ernährungsgewohnheit; Nahrungsmittelkonsum; Einkommenselastizität; Einkommensverteilung; Schätzung; China